Correction to: Effectiveness of mobile SMS based counselling intervention in improving knowledge, attitude and practices of HIV/AIDS patients enrolled in hospitals/NGOs in Terengganu, Malaysia: a mixed mode study protocol - Md Mosharaf Hossain; Ruhani Mat Min; Zikri Muhammad; Kulanthayan K. C. Mani (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.